KESETIAAN: VISI KRISTIANI TENTANG PERKAWINAN YANG UTUH - Kwirinus, Dismas (Sekolah Tinggi Kateketik dan Pastoral Rantepao (STIKPAR) Toraja, 2023)
The focus of this research discusses Fidelity: The Christian Vision of a Whole Marriage. Marriage is a form of human life desired by God. In the Catholic Church, marriage has a noble meaning because Christ himself is present in it. The basic attitude that husbands and wives need to always remember and realize is that the marriage they are in is noble and holy because it was created by God himself. The marriage that they share is a symbol of a divine secret, namely as a symbol of Christ's relationship of love to His Church. Awareness of the nobility and sanctity of marriage will enable them to balance the exposure to tempting internal and external problems. This research uses descriptive qualitative research methods and critical reading of texts. The results of this research are useful for helping married couples and Church officials to appreciate and preserve the noble values of Christian marriage, so that they can combat adultery which is now increasingly common in family life.